Deafness, education and work - Silva, Valéria Simplício da (2020)
The present work aims to show an overview of the state of the art of academic productions, whose theme relates the educational background of the deaf and its work in the labor market, with the purpose is to obtain a deepening in the research process of field research, which makes part of a PhD research, entitled Deafness, education and work: an analysis of this triad in the labor market in Aracaju / Se. For the collection of data, the Bank of Theses and Dissertations of the Coordination of Improvement of Higher Level Personnel (CAPES) was consulted. The search period was initially demarcated by the last year in which the information was available at the Theses Bank, that is, 2018, and five years later, we have as initial cut the year 2014. However, having identified only a production related to this theme, another search was carried out, in general, without delimiting the period, in order to obtain a larger number of published works. For the organization of the data collected and in order to analyze the corpus found, two categories of analysis were defined: (i) types of research; and (ii) theoretical approach. The systematization of the data was done from tables because it was considered that the data presented in them consolidated a quantitative and descriptive analysis. The research in question allows us to know the non-evolution of productions that relate deafness, education and work, since the characterization of productions points to silenced themes, evidencing the need for new investigations in the area.